Larval habitats characteristics of Culicinae subfamily in the south of Iran : Culicinae subfamily in southern of Iran - Sara Doosti; Mohamad Reza Yaghoobi Ershadi; Mohamad Mehdi Sedaghat; Kamran Akbarzadeh; GIDIGLO NUTIFAFA GODWIN (Nusantara Bioscience, 2021)
Abstract. Doosti S, Yaghoobi-Ershadi MR, Sedaghat MM, Akbarzadeh K, Godwin GN. 2021. Larval habitats characteristics of Culicinae subfamily in the south of Iran. Nusantara Bioscience 13: 194-201. Globally, mosquitoes (Diptera: Culicidae) are known vectors of many diseases such as Malaria, Dengue fever, Sindbis, West Nile virus, Rift Vally fever, Japanese encephalitis, and Filariasis. This study aimed to determine larval habitat characteristics of mosquitoes in the south of Iran between 2009 and 2013. The study was carried out in different larval habitats of mosquitoes, and samples were collected using dipping and pipette methods. The larvae were kept in lactophenol solution and transferred to the Medical Entomology of Tehran University of Medical Sciences. Then, microscopic slides were prepared, and species were identified using reliable morphological keys. Characteristics of larval breeding places were investigated based on habitat type, water conditions, vegetation type, and sunlight exposure. A total of 8,188 mosquito larvae were collected from 209 different breeding places. In all, 20 mosquito species belonging to 4 genera were identified. Culex quienquefaciatus, Cx. pipiens, Culiseta longiareolata, Cx. tritaeniorhynchus, Cx. sitiens, Cx. theileri and Aedes caspius were the most common species found in this study. The southern part of Iran has the most wharves and airports. Additionally, there is a high diversity of medically important mosquito species like Cx. pipiens and Cx. tritaeniorhynchus, Ae. albopictus and Ae. vexans from the Culicidae family. The species are capable of vectoring various diseases in the southern part of Iran; hence, there is a need for more investigations.